Study of The Nature, Sources and Avoidance of Dispute and Resolution in Construction Industry - Kuan, Hong Wei (2013)
Construction dispute is found to be very common issue in the construction industry and it has bought negative impact to each participants in a construction project. Therefore, this research study was carried in order to investigate the causes, impact and dispute resolution related to the dispute in construction industry. A questionnaire survey involving 30 responses of constructed players in Malaysia the research objectives are: (1) To recognize the nature and sources of dispute in the construction industry, (2) To identify a guideline and method for avoiding and minimizing the occurrence of dispute in the construction industry, and (3) To overview the procedure of arbitration as one of the prominent dispute resolution method in Malaysia. The survey questionnaire was carried out through online questionnaire. After conducted an analysis based on the returned questionnaires, determine the main source of dispute among the 6 group of source of dispute, which are (1) Determination of agreement, (2) Payment, (3) The site and execution of work, (4) Times, (5) Negligence and nuisance, and (6) Final certificate/payment. Moreover this study also look into construction stages for dispute avoidance, which are (1) Inception stage, (2) Establishment of brief stage, (3) During the design and detailing stage, (4) preparation of tender documentation stage, (5) preparation of tender bid stage, (6) Contract award stage and (7) During the currency of contract/ execution of work stage. Lastly, the procedure of arbitration will be study.sT